CODE MIXING IN BREAK OUT MUSIC PROGRAM ON NET.TV - Siti Nurhayati; Elia Masa Gintings (LINGUISTICA, 2014)
ABSTRACT This research aims to get information of sociolinguistics about code mixing in Break Out Music Program on NET.TV by the presenters. The objectives of the study are to find types of code mixing, and the most dominant type. The research on this thesis was carried out on descriptive qualitative design. The source of data was the whole script of the utterances by the two presenters. The data were the scenes that have code mixing in its dialogue. The data were analyzed based on Muysken theory, there are 104 code mixing used by the two presenters which consists of three types of code mixing which is alternation (62) with total percentage 59,7 %, insertation (34) percentage 32,7 %, and congruent lexicalization (8) 7,7 %. The most dominant type of code mixing used by two presenters of Break Out Music Program on NET.TV is alternation with percentage 59,7 %.   Key words: Code mixing, Break Out Music Program NET. TV